About Some Methods That Contribute To The Development Of Strategic Thinking. / О некоторых методах способствующих развитию стратегического мышления - Mukayev S.B. / Мукаев С.Б. (My University, 2019)
The psychological factors of various diseases, the mechanisms of formation of psychosomatic diseases, the correlation of body and soul are considered.
About Some Methods That Contribute To The Development Of Strategic Thinking. / О некоторых методах способствующих развитию стратегического мышления
Keywords: coronary heart disease, coronary artery bypass grafting, percutaneous coronary intervention, acute coronary syndrome without ST-segment elevation.; приливные явления, гармонический анализ сигналов приливных явлений и оценка их параметров, критерии эффективности обнаружения, спектрально-временной анализ нестационарных процессов, согласованная фильтрация.